2010
DOI: 10.4062/biomolther.2010.18.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Pruritus Research in Atopic Dermatitis

Abstract: -Atopic dermatitis is a common skin disease affecting up to 10% of children and approximately 2% of adults. Atopic dermatitis exhibits four major symptoms, including intense itching, dry skin, redness and exudation. The "itch-scratch-itch" cycle is one of the major features in atopic dermatitis. The pathophysiology and neurobiology of pruritus is unclear. Currently there are no single and universally effective pharmacological antipruritic drugs for treatment of atopic dermatitis. Thus, controlling of itch is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…The majority of drugs used for the treatment of itch, particularly in AD, have been demonstrated to be ineffective. This is due to the sole targeting of the histamine pathways for which histamine is not the only mediator of itch (15). As such, there is an urgent requirement to develop drugs that will target histamine-dependent and histamine-independent itch in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of drugs used for the treatment of itch, particularly in AD, have been demonstrated to be ineffective. This is due to the sole targeting of the histamine pathways for which histamine is not the only mediator of itch (15). As such, there is an urgent requirement to develop drugs that will target histamine-dependent and histamine-independent itch in AD.…”
Section: Discussionmentioning
confidence: 99%
“…small red/purple spots, small and dilated blood vessels on the surface of the skin and skin thinning, atrophy (14). Chronic itch is difficult to treat as current therapeutic options are frequently ineffective, which emphasizes the requirement for more effective therapeutic approaches (15). Furthermore, difficulties are experienced due to the failure of most antihistamines used in AD treatment, as histamine is not the sole mediator of itch (16).…”
Section: Commiphora Myrrha Inhibits Itch-associated Histamine and Il-mentioning
confidence: 99%
“…PAF amplifies the immune response by triggering degranulation, chemotaxis, and adhesion of immune cells, such as eosinophils and MCs [34]. Intradermal injection of PAF can induce wheal and itch, which is related to histamine release from MCs via a neurogenic response because it can be blocked by nerve blocks [35][36][37]. A post hoc analysis in a Japanese study showed that rupatadine, an H1 antihistamine with a PAF antagonist improved total pruritus score in patients with AD [11].…”
Section: Platelet-activating Factor (Paf)mentioning
confidence: 99%
“…A group of pruritogens including inflammatory lipids, cytokines, neuropeptides, neurotransmitters such as histamine and serotonin (5-hydroxytryptamine, 5-HT), proteases, proteinase-activating receptors, and opioid peptides appears to be related to pruritus in AD (Darsow et al , 1997; Steinhoff et al , 2006; Ständer et al , 2008; Lee, 2010). Among these factors, histamine has been the most well-known pruritogen.…”
Section: Specific Features Of Pruritus In Atopic Dermatitismentioning
confidence: 99%
“…Because of the multifactorial pathogenesis of AD, no specific, universally effective and well-tolerated antipruritic agent for AD has been developed yet (Lee, 2010). Until now, management of pruritus in AD is mainly confined to imunomodulators such orgas glucocorticoids, cyclosporin A and topical calcineurin inhibitors (tacrolimus and pimecrolimus) (Wahlgren et al , 1990; Hoare et al , 2000; Hanifin et al , 2001; Luger et al , 2001).…”
Section: Antipruritic Effects Of Immunomodulating Therapy In Atopic Dmentioning
confidence: 99%